Audit Tenure Sebagai Moderasi Fee Audit dan Ukuran Perusahaan Terhadap Kualitas Audit - Neng Asiah; Maulina Dyah Permatasari; Sabaruddinsah Sabaruddinsah; Yulianik Yulianik (Jurnal Eksplorasi Akuntansi, 2024)
Apart from being required to comply with the code of ethics, auditors must also understand client requests. In their involvement with the company, auditors will relate to the audit fees received, the audit period which has an impact on the quality of the resulting audit. This study aims to investigate the impact of audit fees, audit tenure, and audit rotation on audit quality in companies listed on the Indonesia Stock Exchange LQ45 Index from 2020 to 2022. The study employs quantitative data from secondary sources, utilizing documentation as the primary data collection technique. Data analysis is conducted through logistic regression test techniques, with totaling 69 samples. The results show that audit fees have a negative effect on audit quality, while company size has no effect on audit quality. Audit tenure can moderate the effect of audit fees on audit quality, but cannot moderate the effect of company size on audit quality. The discussion further explores the implications of these findings on auditing practices, potential areas for improvement, and considerations for regulatory frameworks.